الثقافة العربية الإسلامية في تعليم اللغة العربية لأغراض دينية: Budaya Arab-Islam dalam pengajaran bahasa Arab untuk tujuan keagamaan - Nyak Mustakim (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
Arabic language and Islamic culture have a very close relationship, in its development the Arabic language become characterizes of islamic culture, and Islamic culture is not regardless of the religion of Islam, therefore the motivation of Arabic language learning is for religious purposes, to study and deepen Islamic studies from Arabic langguage resources like Quran and hadith and turast books. The purpose of this study is to uncover the importence of Islamic culture in arabic learning for religius purpose, and how to present the islamic culture in arabic learning. This study used a library research with qualitative descriptive approach, the data collection in this study is from the books, articel which is directly related to the topic. The results of this study show that input of islamic culture in arabic learning is very importent to understand the relationship between Arabic language and Islamicscience. Delivery of cultural aspects in arabic learning can bedone through language skills, reading, conversation, grammatical rules, literary texts, dictation and calligraphy, in which the topics and examples are derived from Qur'anic texts and hadiths, or from the biographies of the righteous and the Great, or Islamic history, morality and honorable conduct, or Islamic literary texts.